Pengaruh Penambahan Nano-Aditif Ke Dalam Fluida Polyolester Terhadap Gesekan Dan Keausan Material AISI52100 Vs Cast Iron - Ramadhan, Fajar; Fuadi, Zahrul; Kurniawan, Rudi; Rahmadiawan, Dieter; Nasution, Arya Rudi (Rekayasa Material, Manufaktur dan Energi, 2023)
Synthetic lubricants have environment problems because they are difficult to decompose and be-come pollutant materials when disposed into the environment. Therefore, there is an increasing demand for biodegradable lubricants. One of the methods to achieve biodegradability of a lubricant is by using eco-friendly base material and nanoparticles from organic materials as additives, such as nanofibers, cellulose and graphene nanoplatelets. In previous studies, it has been confirmed that applying bacterial cellulose at various volume percentages into polyester (POE) oil has reduced friction and wear of the material up 49%. Other studies also mentioned that the addition of several layers of graphene as an additive to Polyalphaolefin (PAO) oil have decreased the value of the fric-tion coefficient from 0.15 to 0.08. In this study, due to their desirable properties, the bacterial cellu-lose (BC) and graphene nanopartcles were used as additives in polyester (POE) oil. Four types of lubricant specimens with different additive content were prepared for the study. The friction tests were carried out using a reciprocating pin on disk type tribometer at temperatures of 65°±3°C and 27°C. The results indicated improvements in the tribological properties; 60% friction reduction at temperature of 65°±3°C and 66.7% at a temperature of 27°C, with the presence of both BC and graphene in POE compared to those without the additives. In addition, the wear analysis from the results of micro-surface observation of the specimen indicates the reduction of the specific wear rate values as the effect of additives. It is found that the specific wear rate decreased from 6.09×10-6 mm3/N.m to 4.82×10-7 mm3/N.m at 65°±3°C and from 1.57×10-6 mm3/N.m to 2.38×10-7 mm3/N.m at 27°C with the presence of both BC and graphene in POE compared to those without the addi-tives.